2023
DOI: 10.3389/fvets.2023.1045030
|View full text |Cite
|
Sign up to set email alerts
|

Expression of cannabinoid (CB1 and CB2) and cannabinoid-related receptors (TRPV1, GPR55, and PPARα) in the synovial membrane of the horse metacarpophalangeal joint

Abstract: BackgroundThe metacarpophalangeal joint undergoes enormous loading during locomotion and can therefore often become inflamed, potentially resulting in osteoarthritis (OA). There are studies indicating that the endocannabinoid system (ECS) modulates synovium homeostasis, and could be a promising target for OA therapy. Some cannabinoid receptors, which modulate proliferative and secretory responses in joint inflammation, have been functionally identified in human and animal synovial cells.ObjectiveTo characteriz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 133 publications
0
10
0
Order By: Relevance
“…The results of various studies have encouraged the development of new studies supporting the use of molecules acting on these receptors to reduce joint inflammation in horses. This research has provided an anatomical basis for further studies to explore the therapeutic use of non-psychotropic cannabinoids for pain management in horses (2,(42)(43)(44). Research in humans has shown that CBD reduces stress-related signals that can lead to chronic inflammation and pain responses (45).…”
Section: Discussionmentioning
confidence: 92%
“…The results of various studies have encouraged the development of new studies supporting the use of molecules acting on these receptors to reduce joint inflammation in horses. This research has provided an anatomical basis for further studies to explore the therapeutic use of non-psychotropic cannabinoids for pain management in horses (2,(42)(43)(44). Research in humans has shown that CBD reduces stress-related signals that can lead to chronic inflammation and pain responses (45).…”
Section: Discussionmentioning
confidence: 92%
“…Marker for macrophages-the goat anti-IBA1 antibody, recently used on horse tissue [12,14], was directed against a peptide with the sequence C-TGPPAKKAISELP, from the C Terminus of the porcine IBA1 sequence. Horse and porcine IBA1 molecules share 92.3% identity (https://www.uniprot.org/, accessed on 30 June 2019), and it is plausible that the antibody used can also recognise IBA1 in the horse.…”
Section: Specificity Of the Primary Antibodiesmentioning
confidence: 99%
“…There is existing evidence suggesting that cannabinoids may effectively alleviate neuropathic pain and hyperalgesia by inhibiting neuronal transmission in pain pathways [7,8]. Although there is a paucity of university-led research on cannabis therapy in equines, in recent years, some interesting studies have shown beneficial therapeutic effects of cannabinoid molecules in horses with allodynia [9], degenerative painful conditions such as osteoarthritis and laminitis [10,11], and also behavioral disturbances [12]. Consequently, considering the pronounced antinociceptive effects of cannabinoids, they could represent a promising therapeutic approach for the clinical management of TGM headshaking, should the appropriate receptors be expressed in the equine trigeminal ganglion.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, the endocannabinoid system (ECS) has materialised as a possible therapeutic target in veterinary medicine owing to its complicity in a plethora of physiological processes including pain, inflammation, immune function, neurological function, and body homeostasis [ 1 , 2 ]. The ECS consists of the endogenous cannabinoids N-arachidonylethanolamine (anandamide; AEA) and 2-arachidonylglycerol (2-AG), receptors, and enzymes which regulate the synthesis and degradation of endocannabinoids.…”
Section: Introductionmentioning
confidence: 99%
“…The ECS plays a crucial role in maintaining joint health and bone metabolism by modulating the activity of immune cells and reducing inflammation in both tissues, with evidence suggesting that it can regulate bone formation and resorption [ 24 , 25 ]. The mRNA and the immunoreactivity for the CB1R, CB2R, and GPR55 have already been described in the synovial membrane of the metacarpophalangeal joints of horses [ 1 ].…”
Section: Introductionmentioning
confidence: 99%